Estudo da degradação do óleo lubrificante em motores alimentados com biodiesel B100 - Pereira, Flávio Marcos de Melo (2015)
The increasing levels of pollution in urban centers have induced the adoption of mitigating measures in order to reduce negative consequences. In Curitiba, Southern Brazil, the office that regulates urban passenger transport in the city has promoted the use of pure biodiesel (B100) as fuel for a fleet of 34 buses. However, as this measure was put into practice, concerns related to a possible reduction of engine service life were raised, thus forcing the vehicles-owner companies to adopt a conservative maintenance plan, which doubled the frequency of lubricant oil replacement. This was the opportunity for the present study, which aimed to define on a scientific basis the frequency of lubricant oil replacement in engines fueled with biodiesel B100. In order to characterize both the evolution of lubricant oil degradation, as well as the deterioration of lubricant performance due to the use of biodiesel B100, samples of engine lubricant were collected and analyzed along 18 months. Additionally, aiming to confer statistical representativeness to collected data, a population of 7 buses was considered, four of these being fueled with biodiesel B100, while the other 3 with conventional diesel fuel, thus the latter group served as a reference for comparisons. The following parameters of the lubricant oil were measured and analyzed: viscosity, basicity, acidity, oxidation, contamination by soot, contamination by nitrogenous substances, contamination by water, as well as contents of iron, lead, aluminum, copper, chrome, silicon and molybdenum, which are elements typically originated from the wear of metallic components. The conducted study allowed to point out the viscosity as the lubricant parameter that is most sensitive to concomitant use with biodiesel B100. Thus, this parameter was decisive to conclude that based on measured data the service life of the lubricant should be 9900 km for bi-articulated buses, and 13100 km for the articulated ones. It is worth mentioning that the completion of this study became possible by virtue of the collaboration with those companies that took part of the project named LUB-B100, together with the Federal University of Technology - Parana. These companies are Chevron Brasil Lubrificantes (a lubricant maker company), Volvo do Brasil (a bus manufacturer company), Auto Viação Redentor (a company that operates the passenger urban transport in Curitiba), Nórdica Veículos S. A. (a Volvo dealership company) and URBS – Urbanização de Curitiba S. A. (the office that regulates the urban passenger transport in Curitiba).